The Relationship Between The Characteristics of COVID-19 Patients To Predict Mortality in The COVID-19 ICU Special Care - Taufik, Maulana; Wijaya, Dadik Wahyu; Lubis, Andriamuri Primaputra (CoinReads Media Prima, 2022)
Introduction: The SARS-CoV-2 epidemic is sweeping the world with several waves of infections continuing. In some COVID-19 patients, this condition can develop into ARDS (acute respiratory distress syndrome) which requires ICU care with a mortality rate of 50-65 and the need for mechanical ventilation reaches 97%. The aim of this research was to know characteristics of COVID-19 patients to predict mortality in the Negative Pressure Isolation Room COVID 19 ICU at H. Adam Malik General Hospital Method: Retrospective research method with secondary data sources of COVID-19 Negative Pressure Isolation Room ICU (RITN) patients at RSUP H. Adam Malik Medan for the period May 2021 – July 2021.The data collected was in the form of patient data including name, gender, age, medical record number, comorbidities, NLR, D-Dimer, Fibrinogen, PF ratio, use of oxygen supplementation, and length of ICU stay. Chi Square statistical analysis was used for categorical data, while the T-test or Mann Whitney was used for numerical data. Then between the variables an ANOVA test was carried out to assess the comparison of clinical characteristics with mortality. Results: The results of this study indicate a higher mortality rate in women41 people (57.7%), 56-65 years age group 26 people (36.6%), patients using ventilators 51 people (71.8%), comorbid hypertension 33 people (46.5%) ), Moderate PF Ratio were 44 people (62%) and Length of stay <10 days were 55 people (77.5%). The mean fibrinogen value in COVID-19 patients who died was 658.96 ± 674.98, as well as the D-dimer value of 658.96 ± 674.98 and NLR of 11.06 ± 3.23 which showed a significant increase compared to patients Survivors of COVID-19 (p<0.05). Conclusion: A significant relationship was found between gender, age, breathing apparatus, D-dimer, Fibrinogen, NLR and length of stay with mortality of COVID-19 patients treated in the COVID Negative Pressure Room (RITN) ICU